Flotation and Sorptive-Flotation Methods for Removal of Lead Ions from Wastewater Using SDS as Surfactant and Barley Husk as Biosorbent - Ahmed A. Mohammed; Shahlaa E. Ebrahim; Abeer I. Alwared (Journal of Chemistry)
The removal of lead ions from simulated wastewater was investigated using flotation and sorptive-flotation methods. This was achieved by using sodium dodecyl sulfate (SDS) as surfactant and barley husk as biosorbent. Experiments were carried out to study the effect of various parameters such as pH (3, 5, and 8), initial lead ions concentration (25, 50, and 100) mg/L, flow rates (500, 1000, and 1500 mL/min), and SDS concentration (25, 50, and 100) mg/L. The results show that the removal efficiency was enhanced by about 10% when using sorptive-flotation compared with flotation only at the same conditions. Langmuir isotherm model with and high determination coefficient equal to 0.988 was found to give the best fit to the experimental data compared to Freundlich isotherm model with and correlation coefficient equal to 0.94. Pseudo-first-order and pseudo-second-order kinetic models were studied and the results show that the adsorption data correlated with pseudo-first-order kinetic model with equal to 0.122, and this is an indicator to the reversible interaction with equilibrium being established between liquid and solid waste.